The fetal/placental weight ratio is associated with the incidence of atopic dermatitis in female infants during the first 14 months: The Hamamatsu Birth Cohort for Mothers and Children (HBC Study) - Masako Matsumoto, MD; Kenji J. Tsuchiya, MD PhD; Chizuko Yaguchi, MD PhD; Yoshimasa Horikoshi, MD; Naomi Furuta-Isomura, MD PhD; Tomoaki Oda, MD PhD; Yukiko Kohmura-Kobayashi, MD PhD; Naoaki Tamura, MD PhD; Toshiyuki Uchida, MD PhD; Hiroaki Itoh, MD DMedSci (Wolters Kluwer, 2020)
Background: Among atopic diseases, atopic dermatitis is the most common allergic disease in children and influences both infantile and parental quality of life. Objective: The present study investigated the sex-specific relationship between the fetal/placental weight ratio and The incidence of atopic dermatitis in infants during the first 14 months of life. Methods: Study participants were 922 infants (462 female and 460 male) from singleton pregnancies enrolled in the Hamamatsu Birth Cohort for Mothers and Children (HBC Study) after the exclusion of 298 with missing data on atopic dermatitis. The enrollment of infants with atopic dermatitis was based on a positive response from parents regarding whether a physician had ever diagnosed their child with atopic dermatitis by 14 months of age. The two-sample Wilcoxon rank-sum test or χ2 test was adopted for descriptive analyses where appropriate. Unadjusted odds ratios and 95% confidence intervals for the infantile incidence of atopic dermatitis were compared using logistic regression analyses. Results: Maternal and perinatal factors did not correlate with the incidence of infantile atopic dermatitis. Fetal/placental weight ratio, but not birth or placental weight, correlated with the incidence of atopic dermatitis in female, but not male, infants. A correlation was still observed after adjustments for maternal allergies, gestational age at birth, maternal smoking during pregnancy, and household income at birth (odds ratio: 1.57; 95% confidence interval, 1.05-2.33). Conclusion: We speculated that the intrauterine fetal environment, represented by a relatively small placenta, programs a predisposition in only female infants to atopic dermatitis during the first 14 months of life.